Convergence of the numerical solution of the non-linear equation system through the iterations p using the Newton-Raphson algorithm and the Levenberg–Marquardt algorithm. - Martin Dodek (20623832) (2025)
Convergence of the numerical solution of the non-linear equation system through the iterations p using the Newton-Raphson algorithm and the Levenberg–Marquardt algorithm.